MONEY POLITIC DALAM PEMILU PERSPEKTIF HUKUM ISLAM (Studi Analisis Keputusan Lembaga Bahtsul Masail Nahdlatul Ulama) - Umar, Mashudi (JURNAL AT-TURAS, 2015)
In the Indonetion this several years of last in every election of directly many store problem that is money politic. Even, politic often interpreted about interest for power, while money as one of the power based of material. Therefore, money politic is manifestation from someone orientation or commonal in reach aim politic with make money as intermediaries. Practice money politic constitute action that opposite with Constitution momber 10 2008 years about election. For example; implementer, participant and officer of campaign banned promise or provide money or material other to campaigners. That’s why in this articel discussed how exactly money politic in islamic law, especially in view of Nahdlatul Ulama.